WELL TEST ANALYSES ON JATIBARANG VOLCANICS USINGG SINGLE WELL MODELLING - Thawer. R; Sarginson. M; Syahrial. E (Testing Center for Oil and Gas LEMIGAS, 1992)
Well test analyses on the Jatibarang Formation volcanics reservoir in the Jatibarang field were carried out using a numerical simulator with a single radial well model. The volcanics zone is a fractured reservoir with little matrix permeability.